Howard Gardner under fire : the rebel psychologist faces his critics - Schaler, Jeffrey A.; Gardner, Howard (Chicago : Open Court, 2006)
'Thirteen essays criticize Howard Gardner's theories of Multiple Intelligence, ability traits, U-shaped curves in development, and other psychological concepts of spirituality, creativity, and leadership; Gardner responds to each'--Provided by publisher
Includes bibliographical references (p. 347-395) and index
Keywords: Gardner, Howard; Psychology -- Philosophy